If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(x+3)5x=-39
We move all terms to the left:
-2(x+3)5x-(-39)=0
We add all the numbers together, and all the variables
-2(x+3)5x+39=0
We multiply parentheses
-10x^2-30x+39=0
a = -10; b = -30; c = +39;
Δ = b2-4ac
Δ = -302-4·(-10)·39
Δ = 2460
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{2460}=\sqrt{4*615}=\sqrt{4}*\sqrt{615}=2\sqrt{615}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-30)-2\sqrt{615}}{2*-10}=\frac{30-2\sqrt{615}}{-20} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-30)+2\sqrt{615}}{2*-10}=\frac{30+2\sqrt{615}}{-20} $
| 11=-2(3y-5) | | 2=6/g | | 10z=8z+8 | | h+2/2=3 | | -9-4x=59 | | -3(7a-6)=2-5a | | 3x-9=x=+1 | | 32x=2(8x-4) | | 1=x+3/22 | | -3(6-4)+a5=-26-2 | | 22+3n=3(n+5) | | -5(x+1)=-5x-11 | | -6-7x=-6(1+5x) | | 26/r=2 | | t²+2t-15=0 | | -8(1-7x)=-7x-8 | | 6(a+1)=a-29 | | s+1/4=4/ | | -2-7x=-6+3(x+8) | | 8+n/4=-9 | | 2(8-p)=14-3p | | 5(-2p-3)-1=6p | | 7/6y-12=-5 | | 12/4y-13=-1 | | 46x=53x | | 180(n-2)=168*n | | f(1+2)=3f(1+1)-2f(1) | | -7-8r=-47 | | F(x)=x2-5x+2 | | -7-8r=47 | | -2x-7=7x+1+6x | | 6y+3+3y+7=13y-10 |